INTERJECTION IN THE ANTHOLOGY OF SHORT STORIES DREAMING OF THE ORANGE SHADOW BY SANIE B. KUNCORO AS TEACHING MATERIAL FOR INDONESIAN LANGUAGE LESSONS - Ainun Qolbi Munawarotul Fitri; Agus Budi Wahyudi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to identify the form and analyze the function and implications of interjection in the anthology of the short story Mimpi Bayang Jingga by Sanie B. Kuncoro on Indonesian language learning. Using a descriptive qualitative research method with a see-and-take technique, this study found eight types of interjections with a total of 80 appearances that reflected various emotional expressions of the characters, such as astonishment, annoyance, sadness, joy, and invitation. Analysis using matching methods and PUP techniques shows that interjection in texts serves not only as a linguistic element, but also as a stylistic device that reinforces the characterization and atmosphere of the story. The results of this study have implications for Indonesian language learning, especially in the use of literary texts as an authentic learning resource to train students' ability to recognize, understand, and use interjection in real contexts, as well as foster appreciation of literature and character values through expressive and reflective language.